Motor and behavioral symptoms in a case of arachnoid cyst in a young female - Devina Devdatt Dabholkar; V. Ramachandra; Kashmira Rajendra Bhelonde; Archita Gupta (Telangana Journal of Psychiatry)
Arachnoid cysts are rare central nervous system lesions that may have a variable clinical presentation which may cause clinicians to consider a differential diagnosis of a psychiatric disorder. In the case report below, a 22-year-old female presented with headache, disorganized behavior, liability of mood, and altered posture of upper limbs that gradually progressed over a period of 4 months. On neuroimaging, it was found that she had an arachnoid cyst in the left temporal region which might have been the cause of the atypical presentation observed. She was admitted in the psychiatry ward and started on tablet olanzapine, tablet lorazepam, and electroconvulsive therapy (ECT). She improved and behaviorally got better with nearly 100% improvement in symptoms in 28 days. This case demonstrates how it is important to have a high index of suspicion for organicity in the first episode of a psychiatric illness with atypical presentation.